Clinical presentation, management, and outcome in neurolymphomatosis: a systematic review - Kaulen, Leon D.; Hielscher, Thomas; Doubrovinskaia, Sofia; Hoffmann, Dirk C.; Keßler, Tobias; Traub, Benjamin-Leon; Bähring, Joachim; Wick, Wolfgang (Neurology, 2024)
Background and Objectives - Neurolymphomatosis (NL) refers to lymphomatous infiltration of the peripheral nervous system (PNS). NL diagnosis and treatment are challenging given the broad differential diagnosis of peripheral neuropathy, the lack of larger cohorts, and the subsequent unavailability of prognostic factors or consensus therapy. This study aimed to define characteristics and prognostic factors of NL. - Methods - A systematic review of the literature (2004-2023) was performed using PubMed and Scopus databases and reported following PRISMA guidelines. Studies reporting individual patient data on cases with definitive NL diagnosis were included. Clinical, radiologic, pathologic, and outcome information were extracted. Univariable and multivariable survival analyses were performed using log-rank tests and Cox proportional hazard models. - Results - A total of 459 NL cases from 264 studies were accumulated. NL was the first manifestation of malignancy (primary NL) in 197 patients. PNS relapse of known non-Hodgkin lymphoma (secondary NL) occurred in 262 cases after a median 12 months. NL predominantly presented with rapidly deteriorating, asymmetric painful polyneuropathy. Infiltrated structures included peripheral nerves (56%), nerve roots (52%), plexus (33%), and cranial nerves (32%). Diagnosis was established at a median of 3 months after symptom onset with substantial delays in primary NL. It mainly relied on PNS biopsy or FDG-PET, which carried high diagnostic yields (>90%). Postmortem diagnoses were rare (3%). Most cases were classified as B-cell (90%) lymphomas. Tumor-directed therapy was administered in 96% of patients and typically consisted of methotrexate or rituximab-based polychemotherapy. The median overall survival was 18 months. Primary NL without concurrent systemic disease outside the nervous system (hazard ratio [HR]: 0.44; 95% CI 0.25-0.78; p = 0.005), performance status (ECOG <2, HR: 0.30; 95% CI 0.18-0.52; p < 0.0001), and rituximab-based treatment (HR: 0.46; 95% CI 0.28-0.73; p = 0.001) were identified as favorable prognostic markers on multivariable analysis when adjusting for clinical and sociodemographic parameters. - Discussion - Advances in neuroimaging modalities, particularly FDG-PET, facilitate NL diagnosis and offer a high diagnostic yield. Yet, diagnostic delays in primary NL remain common. Rituximab-based therapy improves NL outcome. Findings may assist clinicians in early recognition, prognostic stratification, and treatment of NL.
Online veröffentlicht: 5. August 2024
Gesehen am 05.05.2025